PENGARUH RISIKO USAHA TERHADAP SKOR KESEHATAN BANK UMUM GO PUBLIC DI INDONESIA - Niken Pratiwi (Journal of Business & Banking, 2014)
The purpose of the research is to provide empirical evidence on variables that affect thesoundness score of bank. The variables used to assess business risk are financial ratios,namely LDR, IPR, NPL, IRR, BOPO and FBIR. The research population is the Go-PublicBanks in Indonesia. It uses secondary data obtained from annual financial-reports from 2008to 2012 and InfoBank Magazine from 2009 to 2013. The data were collected by using documentationmethod and then they were processed by using statistical tests as a tool of analysis.The hypothesis testing was done by using the F test to see the effect simultaneously, and usingt test to see the effect partially of LDR, IPR, NPL, IRR, BOPO, and FBIR. Yet, the partialtest (t test) was found that NPL has an effect on soundness score of the bank. When seen fromthe partial coefficient of determination, NPL has the most dominant contribution to thesoundness score of the banks with a value of 14.51 percent.